1999
DOI: 10.1046/j.1365-2141.1999.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic candidiasis in patients with acute leukaemia

Abstract: Summary. A retrospective study of 23 patients with acute leukaemia and hepatosplenic candidiasis (HSC) was conducted to evaluate clinical treatment characteristics in terms of amount and duration of antifungal agents and to assess treatment outcome.Patients were admitted to two major tertiary care centres between 1990 and 1998. The diagnosis of HSC was based on clinical, blood cultures, histologic and imaging studies. Patients were treated with amphotericin B without interruption of the planned chemotherapy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 20 publications
2
47
0
5
Order By: Relevance
“…Detailed clinical and laboratory information of the patients with CDC have been reported previously. 4 Of the 23 patients, 20 patients were in remission, whereas 3 patients had recurring leukemia diagnosed at the time of CDC. Table 1 depicts the characteristics of all patients in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed clinical and laboratory information of the patients with CDC have been reported previously. 4 Of the 23 patients, 20 patients were in remission, whereas 3 patients had recurring leukemia diagnosed at the time of CDC. Table 1 depicts the characteristics of all patients in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Domagk et al [8] also reported a case of common bile duct candidiasis caused simultaneously by C. albicans and C. glabrata. For patients with hematologic malignancies who have suffered from candidal liver abscesses, higher cumulative dosages of AmB (2-9 g) are recommended by most experts, because some evidence reveals that a cumulative dose of less than 2 g AmB correlated with residual lesions at autopsy [1,4,9] . Cases of hepatosplenic candidiasis that were successfully treated with fluconazole have been reported by Kauffman et al The symptoms improved within 3-8 wk, but resolution of lesions on CT scan was noted after at least 1 mo of flu conazole therapy [10 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment experience is mainly available for D-AmB and fluconazole, showing response rates of more than 50% of cases [1,3,15,21,74,98], but caspofungin is today accepted as alternative therapy when the Candida species is not identified [77,105]. If Candida spp.…”
Section: Hepatosplenic Candidosismentioning
confidence: 99%